2020
DOI: 10.1093/mnras/staa3001
|View full text |Cite
|
Sign up to set email alerts
|

Redundant-baseline calibration of the hydrogen epoch of reionization array

Abstract: In 21 cm cosmology, precision calibration is key to the separation of the neutral hydrogen signal from very bright but spectrally-smooth astrophysical foregrounds. The Hydrogen Epoch of Reionization Array (HERA), an interferometer specialized for 21 cm cosmology and now under construction in South Africa, was designed to be largely calibrated using the self-consistency of repeated measurements of the same interferometric modes. This technique, known as redundant-baseline calibration resolves most of the intern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 72 publications
4
44
0
Order By: Relevance
“…In field 2 and 3 where there are bright emissions on the sidelobe, the non-redundancy proves to be higher, with a non-redundancy value of ∼ 6% and ∼ 7% respectively, qualitatively previous works (e.g., Choudhuri et al 2021) have also shown similar results. These values are also well within the 10% non-redundancy estimated by previous studies (e.g., Dillon et al 2020).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In field 2 and 3 where there are bright emissions on the sidelobe, the non-redundancy proves to be higher, with a non-redundancy value of ∼ 6% and ∼ 7% respectively, qualitatively previous works (e.g., Choudhuri et al 2021) have also shown similar results. These values are also well within the 10% non-redundancy estimated by previous studies (e.g., Dillon et al 2020).…”
Section: Resultssupporting
confidence: 91%
“…In summary, our simulations show that, in the presence of bright emissions on the sidelobes, we may expect the power to leak at high 𝑘 values, and the power leakage increases with brightness of sources on the sidelobes. Indeed, previous work by Choudhuri et al (2021) shows similar results, as well as analysis of HERA data (e.g., Kern et al 2020;Dillon et al 2020). In addition, our simulations also show that the presence of bright sources on the main lobe mitigates the power leakage by dominating the overall closure spectra.…”
Section: Simple Sky Modelssupporting
confidence: 75%
See 1 more Smart Citation
“…First-order coupling makes baselines which were otherwise redundant no longer have identical sky responses. For redundantly-configured arrays such as HERA to achieve the measurement sensitivity required to make interferometric measurements of the EoR (the principal scientific goal of the experiment) in any practical duration of observation time, it is imperative, according to analyses such as those presented in Dillon et al (2020), that visibilities from redundant baselines be able to be redundantly averaged -for at least some subset of fringe and delay space. It is beyond the scope of this paper to further address the challenge of nonredundancy caused by array element coupling, but a follow-up study could investigate filtering strategies whereby first-order visibilities of redundant baselines may continue to be identical in certain subsets of fringe and delay space, at least to the level of EoR sensitivity.…”
Section: Mutual Coupling: a Threat To Redundant Baseline Averagingmentioning
confidence: 99%
“…Furthermore, there are several steps that are effectively prerequisite for a subsequent step. For example, an initial calibration solution is determined using a redundant calibration technique [4], after which a sky-referenced calibration is performed [5]. The redundant calibration must be performed before the absolute calibration, though only for each data file specifically.…”
Section: Processingmentioning
confidence: 99%